Workload, work pressure, neutralisation, and interpersonal deviance in public universities in Nigeria - Adeoti, Michael Olalekan; Faridahwati Mohd Shamsudin; AlHamwan, Mohammad Mousa (Penerbit Universiti Kebangsaan Malaysia, 2019)
Extant empirical research on deviant workplace behaviour (DWB) has given less focus on interpersonal deviance. Drawing from the theory of neutralisation and job demand-control model, the present study examined the mediating role of neutralisation in the relationship between workload, work pressure, and interpersonal deviance. Cluster sampling was adopted, and a self-administered questionnaire was used to obtain data from 356 faculty members in public universities in Nigeria. Using partial least squares-structural equation modelling (PLS-SEM), the result revealed that workload and work pressure were significantly related to interpersonal deviance. As expected, neutralisation significantly mediated the positive relationship between workload and interpersonal deviance and between work pressure and interpersonal deviance. The result suggests that faculty members rationalised their interpersonal deviance as a result of workload and work pressure. From the result, the management of Nigerian public universities can minimise the incidence of interpersonal deviance by taking a holistic review of the existing workloads of faculty members and minimise internal conditions that may warrant neutralisation. The outcome of this study provides significant theoretical and practical contributions to organisational behaviour literature.